An update on endometriosis associated subfertility: what does the most recent evidence say? - Abdallah, Karim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Endometriosis is a chronic debilitating disease that affects 10% of women in the reproductive age. Women with endometriosis present with pain, subfertility or both. The prevalence of endometriosis in women with subfertility is estimated to be within the range of 40%-50%. This is a review of the evidence published in the literature. The review was conducted via searching the databases of the Cochrane reviews, European Society of Human Reproduction and Embryology (ESHRE), American Society of Obstetrics and Gynaecology (ACOG), National Institute for Clinical Excellence (NICE) and British Medical Journal (BMJ) best practice articles. Management of women with endometriosis and subfertility has been extensively assessed in the literature. Medical management, surgical approaches and a combination of both improve the spontaneous pregnancy rates for this cohort of patients.